The Benefits of Standards-Based Grading: A Critical Evaluation of Modern Grading Practices - Danielle L. Iamarino (Arizona State University, 2014)
This paper explores the methodology and application of an assessment philosophy known as standards-based grading, via a critical comparison of standards-based grading to other assessment philosophies commonly employed at the elementary, secondary, and post-secondary levels of education. Evidenced by examples of increased student engagement and more thorough comprehension of course materials, standards-based grading is illustrated as an effective replacement for conventional points-based grading. The analysis also identifies and responds to common issues and concerns inherent in the application of standards-based grading, and includes a review of relevant literature and research in support of standards-based grading as a progressive and successful alternative to more conventional assessment philosophies.